(untitled) (REMUNOM, 2024)
The red jambo (Syzygium malaccense L.) is a tropical fruit known for its vibrant red color, which is due to the presence of anthocyanins, a group of natural pigments. In this study, the extract obtained from the fruit peel was used as a natural indicator. Experiments were conducted to evaluate its effectiveness as an acidbase indicator in different pH ranges. The results obtained revealed that the ketone extract demonstrated superior performance in the extraction of anthocyanins present in the samples, exhibiting distinct color changes in acidic and alkaline environments. Its ability to indicate pH variations through visual color changes makes it a practical and accessible choice for classroom demonstrations and laboratory research, contributing to a deeper understanding of fundamental chemistry concepts.